2020
DOI: 10.1186/s13705-019-0232-1
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy for sustainable development in India: current status, future prospects, challenges, employment, and investment opportunities

Abstract: The primary objective for deploying renewable energy in India is to advance economic development, improve energy security, improve access to energy, and mitigate climate change. Sustainable development is possible by use of sustainable energy and by ensuring access to affordable, reliable, sustainable, and modern energy for citizens. Strong government support and the increasingly opportune economic situation have pushed India to be one of the top leaders in the world's most attractive renewable energy markets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(188 citation statements)
references
References 38 publications
(27 reference statements)
1
120
0
1
Order By: Relevance
“…India is the third‐largest producer and consumer of energy. The present installed capacity 356.817 GW as of May 2019 with the share of fossil fuel being 79.8%, and that of renewable sources being 17.3% 41,42 . The Government of India developed various models to promote energy generation from renewable energy sources (RES) 43 to reduce emissions and also reduce the dependency on fossil fuel 44 …”
Section: Model and Scenariosmentioning
confidence: 99%
“…India is the third‐largest producer and consumer of energy. The present installed capacity 356.817 GW as of May 2019 with the share of fossil fuel being 79.8%, and that of renewable sources being 17.3% 41,42 . The Government of India developed various models to promote energy generation from renewable energy sources (RES) 43 to reduce emissions and also reduce the dependency on fossil fuel 44 …”
Section: Model and Scenariosmentioning
confidence: 99%
“…Coal is the primary conventional fuel for energy generation in India, and it contributes about 75 % of the total power generated (Charles Rajesh Kumar & Majid, 2020). Therefore, coal was considered as a 'base case' for comparison with the 'proposed case,' which is wind energy in this study.…”
Section: Emission Reduction Analysismentioning
confidence: 99%
“…This applies to countries of all kinds (developing, industrialized, etc.) (Kumar and Majid 2020 ). Despite this general view, it is observed that wealthy countries appear to be using energy in a manner that is more sustainable today than before 1970.…”
Section: Introductionmentioning
confidence: 99%